Lead acid battery
By using a cast positive electrode current collector composed of a specific lead alloy, the problems of insufficient durability of lead-acid batteries under high temperature conditions and reduction of electrolyte moisture have been solved, achieving high temperature durability and moisture inhibition effects, and reducing costs.
Patent Information
- Application Number
- CN202280061227.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-13
- Filing Date
- 2022-08-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-08-10
AI Technical Summary
Existing lead-acid batteries have insufficient durability and the electrolyte moisture decreases rapidly when used in high-temperature environments, making it difficult to balance high-temperature durability and maintenance-free characteristics.
The positive electrode current collector is manufactured using a lead alloy composition within a specific range, including 0.035-0.08% Ca, 0.50-1.0% Sn, 0.003-0.035% Ag, less than 0.02% Bi and other impurities. The positive electrode current collector is formed by casting, avoiding corrosion and deformation caused by rolling.
It improves the durability of lead-acid batteries at high temperatures and inhibits the reduction of electrolyte moisture, thus extending battery life and reducing manufacturing costs.
Smart Images

Figure CN117957676B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to lead storage batteries. Background Art
[0002] A general lead-acid battery, i.e., a liquid lead-acid battery, has a battery tank having a battery chamber, a plate group housed in the battery chamber, and an electrolyte injected into the battery chamber. The plate group has a plurality of positive plates and negative plates arranged alternately and a separator arranged between the positive plates and the negative plates. The positive plate holds a positive electrode mixture containing a positive electrode active material on a collector plate. The negative plate has a collector plate holding a negative electrode mixture containing a negative electrode active material. Dilute sulfuric acid is used as an electrolyte. Such liquid lead-acid batteries are widely used as automotive batteries, etc.
[0003] In recent years, the engine room of automobiles has become a state where the internal temperature rises significantly due to the increase in equipment and the design of eliminating useless space. Therefore, since liquid lead-acid batteries for automobiles are used in an environment where the positive electrode grid is prone to corrosion or growth (deformation caused by the elongation of the grid), there is a strong demand for countermeasures to extend the life. In addition, liquid lead-acid batteries for automobiles are mostly used in an overcharged state. If used in an overcharged state, the water in the electrolyte is electrolyzed, and the generated hydrogen and oxygen are released to the outside of the battery through the exhaust hole, so the water content of the electrolyte is easily reduced.
[0004] Patent Document 1 describes the alloy composition of the positive electrode collector plate of a maintenance-free lead-acid battery (during the expected life of the battery, maintenance such as water replenishment is only required once or less frequently during use, or preferably not required at all). In addition, in order to provide a maintenance-free lead-acid battery that has a sufficient service life (positive electrode collector plate has good corrosion resistance) even when exposed to a relatively high temperature environment as an SLI battery for automobiles, a positive electrode grid body composed of a lead alloy containing 0.025 to 0.06 mass % of Ca, 0.3 to 0.7 mass % of Sn, and 0.015 to 0.045 mass % of Ag is disclosed.
[0005] It should be noted that the positive electrode collector plate constituting the maintenance-free lead-acid battery has always been formed of a Pb-Ca alloy, and the positive electrode collector plate is formed using a lead alloy to which alloy components such as Sn, Ag, Ba, Cu, Bi, and Se are added depending on the application. Among them, it is known that the corrosion resistance or creep resistance of the positive electrode collector plate is greatly improved by using a lead alloy to which Sn or Ag is added.
[0006] Patent Document 2 discloses that, in order to obtain a long-life lead-acid battery at high temperatures, a positive electrode grid body (positive electrode collector plate) composed of a lead alloy containing 0.05 to 0.085 mass % of Ca, 1.2 to 2.0 mass % of Sn, 0.002 to 0.02 mass % of Bi, 0.0001 to 0.002 mass % of Ag, and 0.005 to 0.03 mass % of Al is used. In addition, it is recorded that by making the alloy composition within the above range, a grid body with excellent workability (strength) can be obtained.
[0007] As lead-acid batteries, in addition to liquid lead-acid batteries, valve-controlled lead-acid batteries can also be cited. Valve-controlled lead-acid batteries have a closed structure with an electrolyte and a laminate, and the laminate is composed of a plurality of positive plates and negative plates arranged alternately and a separator arranged between the positive plates and the negative plates. The electrolyte penetrates into the glass fiber mat as a separator, or gels rather than fluidizes.
[0008] Valve-operated lead-acid batteries are often used for backup power supply applications such as communications, electricity, and disaster prevention, and require less maintenance. Therefore, compared with liquid lead-acid batteries, more emphasis is placed on reducing the reduction of electrolyte water content, and the battery design is such that the battery life cannot be achieved at an early stage due to the reduction of electrolyte water content, so-called liquid depletion.
[0009] The mechanism that causes the reduction of water content in the electrolyte in the valve-controlled lead-acid battery is as follows. The valve-controlled lead-acid battery has a reaction mechanism that suppresses the oxygen generated from the positive plate due to the electrolysis of water during charging from being absorbed by the negative plate due to the oxygen absorption capacity of the negative active material, generates water from the absorbed oxygen, and releases the oxygen generated from the positive plate to the outside of the battery. However, if the amount of oxygen generated in the positive plate exceeds the oxygen absorption capacity of the negative active material, the oxygen in the battery is released from the control valve to the outside of the battery, causing the reduction of water content in the electrolyte.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: U.S. Patent No. 5,298,350
[0013] Patent Document 2: Japanese Patent No. 6406457 Summary of the invention
[0014] Technical problem to be solved by the invention
[0015] However, the lead-acid batteries described in Patent Documents 1 and 2, as lead-acid batteries used under severe conditions such as high-temperature environments, still have room for improvement in achieving both high-temperature durability and maintenance-free characteristics (suppressing the reduction in water content of the electrolyte and eliminating the need for water replenishment).
[0016] The technical problem to be solved by the present invention is to provide a lead-acid battery which has excellent high-temperature durability and can suppress the reduction of water content in the electrolyte.
[0017] Technical solutions for solving technical problems
[0018] In order to solve the above-mentioned technical problems, a first aspect of the present invention provides a lead acid battery having the following structures (1) and (2).
[0019] (1) A method for preparing a device ...
[0020] (2) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of 0.035 mass % to 0.08 mass %, Sn in a range of 0.50 mass % to 1.0 mass %, Ag in a range of 0.003 mass % to 0.035 mass %, Bi in a range of greater than 0 and 0.02 mass %, and the remainder consisting of lead and unavoidable impurities.
[0021] A second aspect of the present invention provides a lead acid battery having the above-mentioned structure (1) and the following structure (3).
[0022] (3) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of 0.035 mass % to 0.07 mass %, Sn in a range of 0.55 mass % to 0.9 mass %, Ag in a range of 0.010 mass % to 0.030 mass %, Bi in a range of 0.0001 mass % to 0.010 mass %, and the remainder consisting of lead and inevitable impurities.
[0023] A third aspect of the present invention provides a lead acid battery having the above-mentioned structure (1) and the following structure (4).
[0024] (4) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of 0.035 mass % to 0.06 mass %, Sn in a range of 0.60 mass % to 0.8 mass %, Ag in a range of 0.015 mass % to 0.025 mass %, Bi in a range of 0.0005 mass % to 0.005 mass %, and the remainder consisting of lead and unavoidable impurities.
[0025] A fourth aspect of the present invention provides a lead acid battery having the above-mentioned structure (1) and the following structure (5).
[0026] (5) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of not less than 0.035 mass % and not more than 0.08 mass %, Sn in a range of not less than 0.50 mass % and not more than 1.0 mass %, Ag in a range of not less than 0.003 mass % and not more than 0.035 mass %, Bi in a range of greater than 0 and not more than 0.02 mass %, Ba in a range of greater than 0 and not more than 0.001 mass %, and the remainder consisting of lead and unavoidable impurities.
[0027] A fifth aspect of the present invention provides a lead acid battery having the above-mentioned structure (1) and the following structure (6).
[0028] (6) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of 0.035 mass % to 0.07 mass %, Sn in a range of 0.55 mass % to 0.9 mass %, Ag in a range of 0.010 mass % to 0.030 mass %, Bi in a range of 0.0001 mass % to 0.010 mass %, Ba in a range of greater than 0 and 0.001 mass %, and the remainder consisting of lead and unavoidable impurities.
[0029] A sixth aspect of the present invention provides a lead acid battery having the above-mentioned structure (1) and the following structure (7).
[0030] (7) The positive electrode collector plate is formed of a lead alloy containing Ca in a range of 0.035 mass % to 0.06 mass %, Sn in a range of 0.60 mass % to 0.8 mass %, Ag in a range of 0.015 mass % to 0.025 mass %, Bi in a range of 0.0005 mass % to 0.005 mass %, Ba in a range of greater than 0 and 0.001 mass %, and the remainder consisting of lead and unavoidable impurities.
[0031] When the lead-acid battery according to the first to sixth aspects of the present invention is a liquid lead-acid battery, the above-mentioned structure (1) has the following structure (11).
[0032] (11) A battery container having a battery chamber, an electrode plate group housed in the battery chamber, and an electrolyte injected into the battery chamber. The electrode plate group has a plurality of positive electrode plates and negative electrode plates arranged alternately and a separator arranged between the positive electrode plates and the negative electrode plates.
[0033] Effects of the Invention
[0034] According to the lead-acid battery of the present invention, it can be expected that both high high-temperature durability and a high effect of suppressing a decrease in water content of the electrolyte can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a partial cross-sectional view showing the structure of a lead acid battery according to one embodiment of the present invention.
[0036] Figure 2 It is a plan view showing a positive electrode current collecting plate constituting a lead acid battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0037] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the embodiments described below. In the embodiments described below, technically preferred limitations are made in order to implement the present invention, but such limitations are not essential conditions for the present invention.
[0038] 〔Overall structure〕
[0039] like Figure 1 As shown, the liquid lead-acid battery of this embodiment includes a battery container 41 having a battery chamber, an electrode group 1 accommodated in the battery chamber, a positive electrode terminal 14 and a negative electrode terminal 24, an electrolyte (not shown) injected into the battery chamber, and a cover 43 fixed to the battery container 41 to block the upper part of the battery chamber. The electrode group 1 includes: a laminate composed of a plurality of positive electrode plates 10 and negative electrode plates 20 arranged alternately and a separator 30 arranged between the positive electrode plates 10 and the negative electrode plates 20; a positive electrode tape 13 connecting the positive electrode plates 10 of the laminate; and a negative electrode tape 23 connecting the negative electrode plates 20 of the laminate.
[0040] One electrode group 1 is accommodated in one battery chamber, and the number of positive electrode plates 10 constituting the stack of electrode group 1 is less than the number of negative electrode plates 20. It should be noted that the number of positive electrode plates 10 may be the same as the number of negative electrode plates 20, or may be greater than the number of negative electrode plates 20.
[0041] The positive electrode plate 10 has a positive electrode collector plate and a positive electrode mixture containing a positive electrode active material. The positive electrode collector plate has a rectangular grid-shaped portion and an ear portion 12 continuous with the grid-shaped portion, and the positive electrode mixture is retained in the grid-shaped portion. The negative electrode plate 20 has a negative electrode collector plate and a negative electrode mixture containing a negative electrode active material. The negative electrode collector plate has a rectangular grid-shaped portion and an ear portion 22 continuous with the grid-shaped portion, and the negative electrode mixture is retained in the grid-shaped portion. The positive electrode mixture and the negative electrode mixture are filled in the openings of the grid-shaped portions of the positive electrode collector plate and the negative electrode collector plate and cover the plate surface of the grid-shaped portion.
[0042] The stack of electrode plates 1 is arranged in the battery container 41 such that the plate surfaces of the grid-shaped portions of the positive electrode plates 10 and the negative electrode plates 20 are along the vertical direction of the battery container 41 .
[0043] The material and manufacturing method of the positive electrode collector plate 11 constituting the positive electrode plate 10 will be described in detail later. The negative electrode collector plate constituting the negative electrode plate 20 is formed by a continuous casting method using a Pb-Ca-Sn alloy. The separator 30 is, for example, a porous film body composed of resin, glass, etc., and a pleated rib protruding in a direction perpendicular to the base surface may be formed on a flat base (film body).
[0044] The ears 12 of the plurality of positive plates 10 are connected by a positive electrode tape 13, and the ears 22 of the plurality of negative plates 20 are connected by a negative electrode tape 23. In addition, one end of a positive electrode terminal 14 is connected to the upper portion of the positive electrode tape 13, and one end of a negative electrode terminal 24 is connected to the upper portion of the negative electrode tape 23. The other ends of the positive electrode terminal 14 and the negative electrode terminal 24 pass through a cover 43 that closes the opening of the battery container 41, and are exposed to the outside of the housing formed by the battery container 41 and the cover 43.
[0045] The electrolyte is dilute sulfuric acid having a specific gravity of 1.28 or more and 1.30 or less (at 20° C.).
[0046] [About the positive plate]
[0047] The positive electrode plate 10 has Figure 2 The positive electrode current collector plate 11 has a rectangular grid-shaped portion 110 and an ear portion 12 protruding from the upper side of the grid-shaped portion 110 .
[0048] The lattice-shaped portion 110 has a frame frame forming four sides of a rectangle and a plurality of inner bones connected to the frame frame and located inside the frame frame. The frame frame includes an upper frame bone 111 located on the upper side of the lattice-shaped portion 110 and extending in a direction perpendicular to the stacking direction (Y direction) of the stacked body and the vertical direction (Z direction) of the battery tank, that is, in a horizontal direction (X direction); a lower frame bone 112 located on the lower side of the lattice-shaped portion 110 and extending in a horizontal direction; and a pair of longitudinal frame bones 113 and 114 extending in a vertical direction (Z direction) of the battery tank. The plurality of inner bones include a plurality of longitudinal inner bones 115 extending from each position of the upper frame bone toward the lower frame bone side and a plurality of transverse inner bones 116 connecting the pair of longitudinal frame bones 113 and 114.
[0049] Furthermore, the positive electrode mixture is filled in all the openings 117 of the grid-like portion 110 , and a layer composed of the positive electrode mixture exists on the entire front and back surfaces of the grid-like portion 110 . That is, the positive electrode mixture is held in the grid-like portion 110 .
[0050] [Regarding the method for manufacturing the positive electrode collector plate]
[0051] As the manufacturing method of the positive collector plate, a casting method using a casting mold, an expansion method or a punching method for processing a rolled substrate, etc. can be listed, but the rolled substrate composed of a Pb-Ca-Sn alloy (a lead alloy containing Ca and Sn as an alloy component) will competitively produce aging, overaging, and recrystallization during rolling. Therefore, in the case where the positive collector plate composed of a Pb-Ca-Sn alloy is a plate (a plate with a rolled structure) obtained by processing a rolled substrate, corrosion is easily generated, and the mechanical strength is reduced due to corrosion, so deformation caused by the elongation of the lattice-shaped portion is easily generated. In contrast, the positive collector plate obtained by the casting method is difficult to deform caused by the elongation of the lattice-shaped portion. Therefore, the positive collector plate composed of a Pb-Ca-Sn alloy is preferably a plate obtained by a casting method, i.e., a plate without a rolled structure (no rolled structure).
[0052] In addition, as a casting method, a gravity casting method, a continuous casting method, etc. are mentioned.
[0053] [About the material of the positive electrode collector plate]
[0054] The positive electrode collector plate 11 is manufactured by casting and is formed of a lead alloy, which contains Ca in a range of not less than 0.035 mass% and not more than 0.08 mass%, Sn in a range of not less than 0.50 mass% and not more than 1.0 mass%, Ag in a range of not less than 0.003 mass% and not more than 0.035 mass%, Bi in a range of greater than 0 and not more than 0.02 mass%, Ba in a range of greater than 0 and not more than 0.001 mass%, and the remainder is composed of lead and inevitable impurities.
[0055] The following describes the effects of each alloy component contained in the above-mentioned lead alloy.
[0056] <Ca(Calcium)>
[0057] The lead alloy forming the positive collector plate contains calcium, and the mechanical strength of the positive collector plate is improved. Specifically, when the positive collector plate is manufactured by casting using the lead alloy, the mechanical strength of the manufactured positive collector plate is improved due to the grain refinement effect of calcium. In addition, when the calcium content is too low, casting defects may sometimes occur. On the other hand, when the calcium content is too high, the necessary corrosion resistance may not be obtained.
[0058] If the content of calcium is in the range of 0.035 mass % or more and 0.08 mass % or less, necessary performance can be obtained in terms of mechanical strength and corrosion resistance. In addition, the content of Ca is preferably in the range of 0.035 mass % or more and 0.07 mass % or less, more preferably in the range of 0.035 mass % or more and 0.06 mass % or less.
[0059] <Sn(Tin)>
[0060] The lead alloy forming the positive collector plate contains tin, and the mechanical strength and corrosion resistance of the positive collector plate are improved. In addition, by increasing the oxygen generation overvoltage of the positive collector plate, the generation of oxygen from the positive plate due to the electrolysis of water can be suppressed. As a result, the reduction of the water content of the electrolyte can be suppressed. If the content of tin is too little, these effects cannot be exerted. On the other hand, when the content of Sn is too much, the cost becomes high.
[0061] If the content of Sn is in the range of 0.50 mass % or more and 1.0 mass % or less, the necessary performance can be obtained in all aspects of mechanical strength, corrosion resistance, oxygen overvoltage and cost. In addition, the content of Sn is preferably in the range of 0.55 mass % or more and 0.90 mass % or less, and more preferably in the range of 0.60 mass % or more and 0.80 mass % or less.
[0062] <Ag(Silver)>
[0063] By making the lead alloy forming the positive collector plate contain silver, the mechanical strength, corrosion resistance and creep resistance of the positive collector plate are improved. If the silver content is too little, these effects cannot be exerted. On the other hand, if the silver content is too much, the oxygen generation overvoltage of the positive collector plate is reduced, the generation of oxygen from the positive plate caused by the electrolysis of water becomes significant, and the cost becomes high.
[0064] If the content of silver is in the range of 0.003 mass % or more and 0.035 mass % or less, the necessary performance can be obtained in all aspects of mechanical strength, corrosion resistance and creep resistance, oxygen generation overvoltage and cost. In addition, the content of Ag is preferably in the range of 0.010 mass % or more and 0.030 mass % or less, and more preferably in the range of 0.015 mass % or more and 0.025 mass % or less.
[0065] <Bi(bismuth)>
[0066] By making the lead alloy forming the positive collector plate contain bismuth, the creep resistance of the positive collector plate is improved. If the bismuth content is too low, this effect cannot be exerted. On the other hand, when the bismuth content is too high, the oxygen generation overvoltage of the positive collector plate is reduced, and the generation of oxygen from the positive plate caused by the electrolysis of water becomes significant.
[0067] If the Bi content is greater than 0 (= 0.0000 mass%) and less than 0.02 mass%, the necessary performance can be obtained in both creep resistance and oxygen overvoltage. In addition, the Bi content is preferably in the range of 0.0001 mass% to 0.010 mass%, and more preferably in the range of 0.0005 mass% to 0.005 mass%.
[0068] <Ba(barium)>
[0069] The lead alloy forming the positive electrode collector plate contains barium, which improves the mechanical strength and corrosion resistance of the positive electrode collector plate. If the content of barium is too low, these effects cannot be exerted. On the other hand, when the content of barium is too high, the cost becomes high.
[0070] When the Ba content is within the range of more than 0 (=0.000 mass%) and 0.001 mass% or less, the effect of improving the mechanical strength and the corrosion resistance can be obtained while suppressing the cost.
[0071] [Function, Effect]
[0072] The liquid lead-acid battery of the embodiment uses a plate made by casting and formed of a lead alloy as the positive electrode collector plate 11, and the lead alloy contains Ca in the range of 0.035 mass% to 0.08 mass%, Sn in the range of 0.50 mass% to 1.0 mass%, Ag in the range of 0.003 mass% to 0.035 mass%, Bi in the range of greater than 0 and 0.02 mass%, Ba in the range of greater than 0 and 0.001 mass%, and the remainder is composed of lead and inevitable impurities. It can take into account both high high-temperature durability and high water reduction inhibition effect of the electrolyte, and can also suppress costs.
[0073] It should be noted that the valve-controlled lead-acid battery can also achieve the same effects as those of the liquid-type lead-acid battery.
[0074] Example
[0075] [Preparation of experimental battery]
[0076] As multiple liquid lead-acid batteries with the same structure as the liquid lead-acid battery of the embodiment, a liquid lead-acid battery with a 5-hour rate capacity of 36Ah, a B24 size, and a nominal voltage of 12V was manufactured, and the liquid lead-acid battery used a positive electrode collector plate with different materials (alloy composition of lead alloy). The battery tank has six battery chambers. All of them have the same structure except the positive electrode collector plate.
[0077] First, as positive electrode collector plates No. 1 to No. 30, lead alloys having alloy compositions of the values shown in Table 1 were produced by gravity casting. Figure 2 The positive electrode collector plate 11 of the shape shown in the figure. At this time, the positive electrode collector plate No. 2 had a casting defect. Specifically, when the cast collector plate was transported to the next process, the collector plate was deformed and could not maintain its shape. Positive electrode collector plates other than No. 2 can be used.
[0078] Next, using a lead alloy having a Ca content of 0.09 mass%, a Sn content of 0.4 mass%, a Ag content of 0.001 mass%, a Bi content of 0.005 mass%, and the remainder consisting of lead and inevitable impurities, a negative electrode collector plate having approximately the same shape as the positive electrode collector plate 11 was produced by continuous casting.
[0079] Next, the lead powder with lead monoxide as the main component and water are kneaded with dilute sulfuric acid, and then necessary additives are further mixed and blended (i.e., by a common method) to prepare a positive electrode mixture paste. Also, the lead powder with lead monoxide as the main component and water are kneaded with dilute sulfuric acid, and then necessary additives are further mixed and blended (i.e., by a common method) to prepare a negative electrode mixture paste.
[0080] The obtained positive electrode mixture paste is uniformly applied and filled on the entire surface of the grid-shaped portion of the positive electrode collector plate, and then preheated and dried and aged by a common method to produce a positive electrode plate (before formation). In addition, the obtained negative electrode mixture paste is uniformly applied and filled on the entire surface of the grid-shaped portion of the negative electrode collector plate, and then preheated and dried and aged by a common method to produce a negative electrode plate (before formation).
[0081] Next, for each sample, the negative electrode plate before formation was placed in a polyethylene bag-shaped separator, and the 7 separators containing the negative electrode plate before formation and the 6 positive electrode plates before formation were alternately stacked to obtain a laminate. Next, a casting device of the COS (cast strip) method was used to form a belt, an intermediate pole and a terminal pole on the positive electrode plate and the negative electrode plate before formation of each laminate, thereby obtaining a plate group.
[0082] Six electrode groups are prepared for each sample and placed in each battery chamber of a battery container. The usual steps are performed, including resistance welding of the intermediate poles between adjacent battery chambers, heat welding of the battery container and the cover, injection of electrolyte into each battery chamber from each filling port, and plugging of the filling port with a liquid plug, etc., thereby assembling liquid lead-acid batteries (before formation) for No. 1, No. 3 to No. 30.
[0083] The electrolyte solution was injected by injecting dilute sulfuric acid having a specific gravity of 1.250 (20° C. converted value) into each battery chamber.
[0084] Then, the battery tank was formed so that the specific gravity of the electrolyte after the battery tank formation was 1.285 (20° C. conversion value), thereby obtaining two lead storage batteries No. 1 and No. 3 to No. 30, respectively.
[0085] [Determination of the composition of lead alloy]
[0086] One of the two lead-acid batteries obtained was disassembled, and the alloy composition of the positive electrode current collector plate (after chemical formation) was measured.
[0087] Specifically, first, the electrode group is taken out from the battery room (first battery room) containing the electrode group with the positive terminal pole, and the electrode group is disassembled, and the positive electrode plate arranged on the side of the fourth battery room is taken out. Next, the ear of the positive electrode collector plate is cut off from the taken out positive electrode plate, and the surface of the ear is grinded to expose the metallic glossy surface. Next, the grinded ear is used as a sample, and quantitative analysis is performed using a solid-state light emission analyzer (OES: "PDA-7000" manufactured by Shimadzu Corporation) using a conventionally known method.
[0088] [Experiments and evaluations]
[0089] As a test for evaluating high temperature durability, a light load life test specified in “JISD 5301: 2019” was performed under the condition of 75° C. using the remaining one of the two lead-acid batteries obtained.
[0090] Specifically, each lead-acid battery was placed in a water tank at 75°C, and discharged (240±1 seconds at a discharge current of 25.0±0.1A) and charged (600±1 seconds at 14.80V±0.03V), and the liquid reduction (the amount of water in the electrolyte decreased) was measured, and the same amount of purified water as the liquid reduction was replenished and the life was determined every 480 cycles. In the life determination, each lead-acid battery was continuously discharged for 30 seconds at a rated cold cranking current, and the life was determined when the voltage was 7.2V or less at the 30th second.
[0091] Regarding the determination of the amount of liquid reduction, the mass of the battery was measured every 480 cycles, and the amount of reduction from the mass before the experiment was calculated as the amount of liquid reduction. Then, the cumulative amount of liquid reduction at the end of 1920 times was investigated (the total value of the amount of liquid reduction calculated every 480 times). For samples that reached the end of their life before the number of cycles (number of repeated discharge and charge) reached 1920 times, the cumulative amount of liquid reduction was not measured.
[0092] These experimental results are shown in Table 1 together with the composition of the lead alloy forming the positive electrode current collector plate of each lead storage battery and the determination of the cost of the lead alloy.
[0093] The cost of the lead alloy is judged as “◎” when it is the same as or 1.05 times or less than the cost of the lead alloy used in No. 1, “○” when it is more than 1.05 times and less than 1.08 times, “△” when it is more than 1.08 times and less than 1.10 times, and “×” when it is more than 1.10 times.
[0094] In addition, the high temperature durability in the experimental results is judged as the required high temperature durability standard is more than 2000 cycles, so the case of less than 2000 cycles is recorded as "×", the case of more than 2000 cycles and less than 4000 cycles is recorded as "○", and the case of more than 4000 cycles is recorded as "◎". The judgment of the liquid reduction characteristics (whether the reduction of the electrolyte is suppressed) is recorded as "◎" when the cumulative liquid reduction at the time point of 1920 cycles is less than 350g, the case of more than 350g and less than 400g is recorded as "○", and the case of more than 400g is recorded as "×".
[0095] In addition, a comprehensive judgment based on the experimental results was performed as follows. When all judgments were "◎", it was recorded as "◎". When any one of the high-temperature durability, liquid reduction characteristics and cost was judged as "○", it was recorded as "○". When any one of the high-temperature durability, liquid reduction characteristics and cost was judged as "△", it was recorded as "△". When any one of the high-temperature durability, liquid reduction characteristics and cost was judged as "×", it was recorded as "×".
[0096] [Table 1]
[0097]
[0098] From the results in Table 1, we can know the following.
[0099] <No.1>
[0100] The lead acid battery No. 1 is a conventional example used as a cost basis. As a result, the life obtained in the light load life test at 75° C. (a test for evaluating high temperature durability) was 1920 cycles, and the cumulative liquid reduction was 400 g.
[0101] The calcium content of the lead alloy forming the positive collector plate of the lead-acid battery of No. 1 is 0.090% by mass, which is more than the upper limit of the calcium content of the lead alloy (hereinafter referred to as the "first lead alloy") forming the positive collector plate of the lead-acid battery of the first mode. In addition, the tin content of the lead alloy forming the positive collector plate is 1.10% by mass, which is more than the upper limit of the tin content of the first lead alloy. In addition, the lead alloy forming the positive collector plate does not contain silver as a necessary component of the first lead alloy. In addition, the bismuth content of the lead alloy forming the positive collector plate is 0.0200% by mass, which is more than the upper limit of the bismuth content of the lead alloy (hereinafter referred to as the "second lead alloy") forming the positive collector plate of the lead-acid battery of the second mode.
[0102] Thus, in the lead-acid battery No. 1, the composition of the lead alloy forming the positive electrode collector plate has an excessive calcium content compared to the first lead alloy, and since it does not contain silver, the corrosion resistance of the positive electrode collector plate is insufficient, and since there is slightly more bismuth (more than the second lead alloy), the performance of suppressing the reduction of electrolyte is insufficient.
[0103] <No.2>
[0104] The positive electrode collector plate No. 2 is formed by a lead alloy whose contents of tin, silver, bismuth and barium in the alloy components are within the range of the lead alloy forming the positive electrode collector plate of the fifth type of lead-acid battery (hereinafter referred to as the "fifth lead alloy"), and whose calcium content is lower than the lower limit value of the calcium content of the lead alloy forming the positive electrode collector plate of the fourth type of lead-acid battery (hereinafter referred to as the "fourth lead alloy").
[0105] It is considered that the positive electrode current collector plate of No. 2 had a casting defect because the calcium content of the lead alloy forming the positive electrode current collector plate was 0.030 mass %, which was lower than the lower limit of the calcium content of the fourth lead alloy.
[0106] <No.3~No.8>
[0107] The contents of tin, silver and bismuth in the lead alloy forming the positive collector plate of the lead-acid batteries No. 3 to No. 8 are the same within the range of the lead alloy forming the positive collector plate of the third type of lead-acid battery (hereinafter referred to as the "third lead alloy") and the lead alloy forming the positive collector plate of the sixth type of lead-acid battery (hereinafter referred to as the "sixth lead alloy"), the barium content is 0.001 mass % (within the range of the sixth alloy) or 0.000 mass % (within the range of the third alloy), and the calcium content is different (within the range of the first and fourth alloys).
[0108] Lead-acid batteries No. 3 to No. 8 can obtain excellent high-temperature durability of more than 2,500 cycles and particularly excellent liquid reduction characteristics of less than 350 g of cumulative liquid reduction. In addition, compared with the lead-acid battery No. 1, the silver content of the lead alloy forming the positive electrode collector plate is high, but the content of calcium and tin is low, so the manufacturing cost can be reduced. In particular, since the price of tin is high, the tin content can be reduced to about half, thereby greatly reducing the material cost.
[0109] The lead alloys forming the positive electrode collector plates of the lead-acid batteries No. 3, No. 5 to No. 8 have the same contents of tin, silver, bismuth and barium (within the range of the sixth alloy), and different calcium contents within the range of the fourth alloy. The calcium content of the lead alloy forming the positive electrode collector plate of No. 7 is outside the range of the sixth alloy, and the calcium content of the lead alloy forming the positive electrode collector plate of No. 8 is outside the range of the fifth alloy.
[0110] Among the lead-acid batteries No. 3, No. 5 to No. 8, the lead-acid batteries No. 3, No. 5 and No. 6 have a positive electrode collector plate formed of a lead alloy having not only tin, silver, bismuth and barium but also a calcium content within the range of the sixth alloy, thereby obtaining particularly excellent high-temperature durability of more than 4000 cycles and particularly excellent liquid reduction characteristics with a cumulative liquid reduction of less than 350 g.
[0111] In addition, if No. 4 and No. 5, which differ only in the barium content of the lead alloy forming the positive electrode collector plate, are compared, the lead-acid battery No. 5 having a positive electrode collector plate formed of a lead alloy containing 0.001 mass % of barium has excellent high-temperature durability compared to the lead-acid battery No. 4 having a positive electrode collector plate formed of a lead alloy containing no barium (0.000 mass %).
[0112] <No.5、No.9~No.15>
[0113] The contents of calcium, silver, bismuth and barium in the lead alloy forming the positive electrode collector plate of the lead-acid batteries No. 5, No. 9 to No. 14 are within the range of the fourth alloy, and the contents of tin are different. The contents of calcium, bismuth and barium in the lead alloy forming the positive electrode collector plate of the lead-acid battery No. 15 are within the range of the fourth alloy, and the contents of silver and tin are outside the range of the fourth alloy.
[0114] Among the lead-acid batteries of No. 5, No. 9 to No. 15, the lead-acid batteries of No. 5, No. 10 to No. 14 have a positive electrode collector plate formed of a lead alloy having not only calcium, silver, bismuth and barium but also a tin content within the range of the fourth alloy, and thus have excellent high-temperature durability of more than 3,000 cycles and excellent liquid reduction characteristics of less than 400 g of cumulative liquid reduction. The lead-acid battery of No. 15 has a significantly increased manufacturing cost because the tin content of the alloy forming the positive electrode collector plate is greater than the upper limit of the fourth alloy.
[0115] Among the lead-acid batteries No. 5, No. 10 to No. 14, the lead-acid batteries No. 5, No. 12 to No. 14 have a positive electrode collector plate formed of a lead alloy in which calcium, silver, bismuth and barium are within the range of the sixth alloy and the tin content is within the range of 0.060 mass % and 1.0 mass %, thereby obtaining more excellent high-temperature durability of more than 4000 cycles and particularly excellent liquid reduction characteristics with a cumulative liquid reduction of less than 350 g.
[0116] Among the lead-acid batteries of No. 5, No. 12 to No. 14, the lead-acid batteries of No. 5 and No. 12 have a positive electrode current collector plate formed of a lead alloy having not only calcium, silver, bismuth and barium but also a tin content within the range of the sixth alloy, thereby reducing costs compared to the lead-acid batteries of No. 13 and No. 14, and obtaining particularly excellent high-temperature durability of more than 4,500 cycles, which is higher than the lead-acid batteries of No. 13 and No. 14. That is, by having a positive electrode current collector plate formed of a lead alloy within the range of the sixth alloy, a cost reduction effect, particularly excellent high-temperature durability and excellent liquid reduction characteristics are obtained.
[0117] <No.5、No.16~No.23>
[0118] The contents of calcium, tin, bismuth, and barium in the lead alloy forming the positive electrode current collector plate of the lead storage batteries of No. 5 and No. 16 to No. 23 were within the range of the fourth alloy, and the contents of silver were different.
[0119] Among the lead-acid batteries No. 5, No. 16 to No. 23, the lead-acid batteries No. 5, No. 19 to No. 22 have a positive electrode collector plate formed of a lead alloy having a silver content within the range of the fourth alloy and having excellent high-temperature durability of more than 3,000 cycles and particularly excellent liquid reduction characteristics of less than 350 g of cumulative liquid reduction.
[0120] Among the lead-acid batteries No. 5, No. 19 to No. 22, the lead-acid batteries No. 5, No. 19 and No. 20 have a positive electrode collector plate formed of a lead alloy having not only calcium, tin, bismuth and barium but also a silver content within the range of the sixth alloy, thereby achieving particularly excellent high-temperature durability of more than 4,500 cycles and a high cost reduction effect.
[0121] In addition, the lead-acid batteries No. 5, No. 20 to No. 22 have a positive electrode collector plate formed of a lead alloy in which calcium, tin, bismuth and barium are within the range of the sixth alloy and the silver content is within the range of 0.020 mass % and 0.035 mass %, thereby achieving significantly excellent high-temperature durability of more than 4,800 cycles.
[0122] <No.5、No.24~No.30>
[0123] The contents of calcium, tin, silver, and barium in the lead alloy forming the positive electrode current collector plate of the lead storage batteries of No. 5 and No. 24 to No. 30 were within the range of the fifth alloy, but the contents of bismuth were different.
[0124] Among the lead-acid batteries No. 5, No. 24 to No. 30, the lead-acid batteries No. 5, No. 25 to No. 29 have a positive electrode collector plate formed of a lead alloy in which the content of calcium, tin, silver and barium is within the range of the fifth alloy and the content of bismuth is within the range of the fourth alloy, thereby obtaining excellent high-temperature durability of more than 3,500 cycles and excellent liquid reduction characteristics with a cumulative liquid reduction of less than 400 g.
[0125] Among the lead-acid batteries No. 5, No. 25 to No. 29, the lead-acid batteries No. 5, No. 26 and No. 27 have a positive electrode collector plate formed of a lead alloy having not only calcium, tin, silver and barium but also a bismuth content within the range of the sixth alloy, thereby achieving particularly excellent high-temperature durability of more than 4,500 cycles and a high cost reduction effect, as well as particularly excellent liquid reduction characteristics with a cumulative liquid reduction of less than 350 g.
[0126] In the production of lead acid battery No. 24, the positive electrode collector plate was formed using a lead alloy obtained by completely removing Bi from a commercially available lead alloy (containing a small amount of Bi). Since the bismuth removal step is expensive, the cost is high.
[0127] In addition, the lead-acid battery No. 24 is an example of using a positive electrode collector plate composed of a lead alloy as described in Patent Document 1, and the high temperature durability is as short as 1917 cycles. After the experiment, the battery was disassembled, and the result confirmed that significant growth was generated in the grid-shaped portion of the positive electrode collector plate. Therefore, it can be considered that the positive electrode mixture falls off from the grid-shaped portion of the positive electrode collector plate is the cause of the short life.
[0128] Description of Reference Numerals
[0129] 1: electrode plate group; 10: positive electrode plate; 11: positive electrode collector plate; 12: ear portion of positive electrode collector plate; 110: grid-like portion of positive electrode collector plate; 111: upper frame frame; 112: lower frame frame; 113: longitudinal frame frame; 114: longitudinal frame frame; 115: longitudinal inner frame; 116: transverse inner frame; 117: opening; 13: positive electrode belt; 14: positive terminal; 20: negative electrode plate; 22: ear portion of negative electrode collector plate; 23: negative electrode belt; 24: negative terminal; 30: diaphragm; 41: battery container; 43: cover.
Claims
1. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of alternately arranged positive plates and negative plates and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.08 mass%, Sn in a range of 0.50 mass% to 1.0 mass%, Ag in a range of 0.003 mass% to 0.035 mass%, Bi in a range of greater than 0 and less than 0.005 mass%, and the remainder is composed of lead and inevitable impurities.
2. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of alternately arranged positive plates and negative plates and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.07 mass%, Sn in a range of 0.55 mass% to 0.9 mass%, Ag in a range of 0.010 mass% to 0.030 mass%, Bi in a range of 0.0001 mass% to less than 0.005 mass%, and the remainder is composed of lead and inevitable impurities.
3. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of alternately arranged positive plates and negative plates and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.06 mass%, Sn in a range of 0.60 mass% to 0.8 mass%, Ag in a range of 0.015 mass% to 0.025 mass%, Bi in a range of 0.0005 mass% to less than 0.005 mass%, and the remainder is composed of lead and inevitable impurities.
4. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of alternately arranged positive plates and negative plates and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.08 mass%, Sn in a range of 0.50 mass% to 1.0 mass%, Ag in a range of 0.003 mass% to 0.035 mass%, Bi in a range of greater than 0 and less than 0.005 mass%, Ba in a range of greater than 0 and 0.001 mass%, and the remainder is composed of lead and inevitable impurities.
5. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of positive plates and negative plates arranged alternately and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.07 mass%, Sn in a range of 0.55 mass% to 0.9 mass%, Ag in a range of 0.010 mass% to 0.030 mass%, Bi in a range of 0.0001 mass% to less than 0.005 mass%, Ba in a range of greater than 0 and less than 0.001 mass%, and the remainder is composed of lead and inevitable impurities.
6. A lead-acid battery, comprising an electrolyte and a laminate, The stacked body is composed of a plurality of alternately arranged positive plates and negative plates and a separator arranged between the positive plates and the negative plates. The positive electrode plate includes a positive electrode mixture containing a positive electrode active material and a positive electrode current collector plate including a grid-shaped portion holding the positive electrode mixture. The positive electrode collector plate is formed of a lead alloy, which contains Ca in a range of 0.035 mass% to 0.06 mass%, Sn in a range of 0.60 mass% to 0.8 mass%, Ag in a range of 0.015 mass% to 0.025 mass%, Bi in a range of 0.0005 mass% to less than 0.005 mass%, Ba in a range of greater than 0 and less than 0.001 mass%, and the remainder is composed of lead and inevitable impurities.
7. The lead acid battery according to any one of claims 1 to 6, wherein The positive electrode collector plate is obtained by a casting method.
Citation Information
Patent Citations
Wall panel mount jig
JP1989006457A
Calcium-tin-silver lead-based alloys, and battery grids and lead-acid batteries made using such alloys
US5298350A
Lead storage cell and electrode collector for lead storage cell
CN106133967A
Grid alloy for high-temperature circulating type AGM battery and preparation method thereof
CN110284026A
Lead-based alloy for lead-acid battery
CN1692170A